Internalisasi Nilai-Nilai Spiritual: Kemandirian ODGJ melalui Activity of Daily Living - Nurhilal, Nazwa Azkia; Rahmawati, Lutfia (Assertive: Islamic Counseling Journal, 2024)
Abstract: Mental disorders can cause limited independence in carrying out daily activities or Activities of Daily Living (ADL). Spiritual activities are very necessary for people with mental disorders (ODGJ) considering changes in their mental status. This research aims to determine the internalization of spiritual values ​​and independence for ODGJ through Activities of Daily Living (ADL) carried out at the Tirto Jiwo Psychosocial Rehabilitation Home. This research uses qualitative research with a case study type. Data collection was carried out by conducting interviews with subjects, namely the management of the Tirto Jiwo Psychosocial Rehabilitation Home, Purworejo, Central Java, and conducting observations, and then the results of the research data were analyzed and then used to discuss the research results. The result of this research is that ODGJ learn to internalize spiritual values ​​to increase the independence of people with mental disorders. A spiritual approach also contributes to increasing self-awareness, inner calm, and emotional control for ODGJ. The integration of spiritual values ​​in rehabilitation programs not only improves mental well-being but also encourages independence and active participation in spiritual activities according to the abilities of ODGJ.   Abstrak: Gangguan jiwa dapat menyebabkan keterbatasan kemandirian dalam melakukan kegiatan sehari-hari atau Activity of Daily Living (ADL). Aktivitas spiritual sangat diperlukan pada orang dengan gangguan jiwa (ODGJ) mengingat dalam perubahan status mentalnya. Penelitian ini bertujuan untuk mengetahui internalisasi nilai-nilai spiritual dan kemandirian ODGJ melalui Activity of Daily Living (ADL) yang dilakukan di Panti Rehabilitasi Psikososial Tirto Jiwo. Penelitian ini menggunakan penelitian kualitatif dengan jenis studi kasus. Pengumpulan data dilakukan dengan melakukan wawancara kepada subyek yaitu pengelola Panti Rehabilitasi Psikososial Tirto Jiwo Purworejo Jawa Tengah, dan juga melakukan observasi, kemudian hasil data penelitian dilakukan analisis data untuk kemudian dipakai untuk pembahasan hasil penelitian. Hasil dari penelitian ini adalah ODGJ belajar melakukan internalisasi nilai-nilai spiritual untuk meningkatkan kemandirian orang dengan gangguan jiwa. Pendekatan spiritual juga berkontribusi pada peningkatan kesadaran diri, ketenangan batin dan pengendalian emosi ODGJ. Integrasi nilai-nilai spiritual dalam program rehabilitasi tidak hanya meningkatkan kesejahteraan mental, tetapi juga mendorong kemandirian dan partisipasi aktif dalam kegiatan spiritual sesuai dengan kemampuan ODGJ.